2009
DOI: 10.1002/cne.22033
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of subventricular zone neural precursors induces an endogenous precursor cell response in a rat model of Parkinson's disease

Abstract: Realistically, future stem cell therapies for neurological conditions including Parkinson's disease (PD) will most probably entail combination treatment strategies, involving both the stimulation of endogenous cells and transplantation. Therefore, this study investigates these two modes of neural precursor cell (NPC) therapy in concert in order to determine their interrelationships in a rat PD model. Human placental alkaline phosphatase (hPAP) labeled NPCs were transplanted unilaterally into host rats which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 63 publications
6
59
0
Order By: Relevance
“…5,17 The expression of hPAP allows identification of grafted NPCs, labeled with this human marker, within the brains of wild-type host rats. 17,18 The NSCs were grown in uncoated dishes in proliferation medium consisting of serum-free Neurobasal-A (Thermo Fisher Scientific, Waltham, MA, USA) supplemented with 20 ng/mL epidermal growth factor (Cell Sciences, Canton, MA, USA), 10 ng/mL basic fibroblast growth factor (Cell Sciences), 2 μg/ mL heparin (STEMCELL Technologies, Vancouver, BC, Canada), 2% B27 (Thermo Fisher Scientific), 1% glutamax (Thermo Fisher Scientific), and 1% antibiotic-antimycotic (Thermo Fisher Scientific).…”
Section: Nsc Culturementioning
confidence: 99%
See 3 more Smart Citations
“…5,17 The expression of hPAP allows identification of grafted NPCs, labeled with this human marker, within the brains of wild-type host rats. 17,18 The NSCs were grown in uncoated dishes in proliferation medium consisting of serum-free Neurobasal-A (Thermo Fisher Scientific, Waltham, MA, USA) supplemented with 20 ng/mL epidermal growth factor (Cell Sciences, Canton, MA, USA), 10 ng/mL basic fibroblast growth factor (Cell Sciences), 2 μg/ mL heparin (STEMCELL Technologies, Vancouver, BC, Canada), 2% B27 (Thermo Fisher Scientific), 1% glutamax (Thermo Fisher Scientific), and 1% antibiotic-antimycotic (Thermo Fisher Scientific).…”
Section: Nsc Culturementioning
confidence: 99%
“…Multiple concentrations and times of MIRB treatment (5,10,20,50,60,80, and 100 μg Fe/mL for 18, 20, 30, or 48 hours) were first tested to assess NSC labeling ( Figure S1). These experiments indicated that both 20 and 50 μg doses when applied for 20 hours resulted in optimal labeling of the NSCs as visualized by Prussian blue staining and under rhodamine fluorescence.…”
Section: Nsc Labeling With Mirbmentioning
confidence: 99%
See 2 more Smart Citations
“…Presence of neurogenesis in the SNc suggests that disease progression may rely on the loss of dopaminergic neurons as well as on the malfunctioning in their turnover. Possible efficacy of orthotopic dopaminergic neurogenesis in PD has been questioned for a long time (Hermann and Storch, 2008), but transplantation experiments have indicated that several SC types, including neural precursors (Arias-Carrion et al, 2006;Madhavan et al, 2009) and MSC , can significantly support endogenous neurogenesis during the degenerative process in animal models of PD (Hess and Borlongan, 2008). Neurogenesis has been confirmed in SVZ of human brains (Curtis et al, 2007), but its physiological role is still uncertain .…”
Section: Neurorepair/neurogenesismentioning
confidence: 99%